2015
DOI: 10.1371/journal.pone.0141883
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation, Stress, and Life Stage: A Systematic Data Collection Study among Women in Odisha, India

Abstract: Emerging evidence demonstrates how inadequate access to water and sanitation is linked to psychosocial stress, especially among women, forcing them to navigate social and physical barriers during their daily sanitation routines. We examine sanitation-related psychosocial stress (SRPS) across women’s reproductive lives in three distinct geographic sites (urban slums, rural villages, and rural tribal villages) in Odisha, India. We explored daily sanitation practices of adolescent, newly married, pregnant, and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 29 publications
7
110
1
2
Order By: Relevance
“…Water rationing and uncertainties over water supply times may engender feelings of anxiety. Women's inability to perform these tasks leads to feelings of inadequacy, shame, fear, worry, and anxiety that ultimately leads to poor mental health (Hulland et al, ; Workman & Ureksoy, ). When women are incapable of performing duties that are traditionally important and expected, such as keeping houses clean for visitors, helping their families to maintain proper hygiene, and ensuring that their families are clean and able to participate in public functions, feelings of anxiety and mental illnesses may develop (Stevenson et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water rationing and uncertainties over water supply times may engender feelings of anxiety. Women's inability to perform these tasks leads to feelings of inadequacy, shame, fear, worry, and anxiety that ultimately leads to poor mental health (Hulland et al, ; Workman & Ureksoy, ). When women are incapable of performing duties that are traditionally important and expected, such as keeping houses clean for visitors, helping their families to maintain proper hygiene, and ensuring that their families are clean and able to participate in public functions, feelings of anxiety and mental illnesses may develop (Stevenson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…When women are incapable of performing duties that are traditionally important and expected, such as keeping houses clean for visitors, helping their families to maintain proper hygiene, and ensuring that their families are clean and able to participate in public functions, feelings of anxiety and mental illnesses may develop (Stevenson et al, ). For example, women in urban areas of Odisha, noted that the most stressful aspect of their sanitation experiences was the need to carry water every day, sometimes getting wet on rainy days and walking through mud (Hulland et al, ). The same study found that defecation, menstruation, and cleaning duties were constant sources of stress related to water and sanitation and insecurity (Hulland et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Alguns autores defendem que o conceito de rural, além de aspectos demográficos, é definido também por condições socioeconômicas e territoriais relacionadas com os modos de reprodução social (WANDERLEY;FAVARETO, 2013;ABRAMOVAY, 2000). Nas três comunidades em estudo, a associação comunitária representa uma forte organização social que promove a união dos moradores e cumpre o papel de buscar direitos e benefícios para a localidade que A ausência de instalação sanitária é apontada por alguns estudos como um dos fatores que impactam, sobremaneira, a vida das mulheres (HULLAND et al, 2015;KWIRINGIRA et al, 2014). Além disso, devido às divisões de trabalho usualmente adotadas nas áreas rurais -onde o homem é responsável pelo trabalho agrícola e o sustento da casa, e a mulher é a responsável pelo trabalho doméstico -, as mulheres se envolvem mais com as ações sanitárias, sendo as responsáveis pelo acesso à água e sua gestão cotidiana no nível domiciliar e pela queima dos resíduos sólidos.…”
Section: A Inter-relação Entre Ruralidade E Saneamento Básico: Um Olhunclassified
“…22 30 31 Poor water and sanitation access can also affect the social, physical and mental well-being of women, acting through pathways ranging from unsafe menstrual hygiene management practices and increased risk of violence. [32][33][34] Description of the intervention Over the past few decades, there has been a global commitment to determine water and sanitation interventions with demonstrated effectiveness, not just efficacy. 35 Gram Vikas, a non-governmental organisation based in Odisha, India (http://www.gramvikas.org/), has responded by implementing its MANTRA (Movement and Action Network for Transformation of Rural Areas) water and sanitation programme in more than 1000 villages since 2002.…”
Section: Introductionmentioning
confidence: 99%